Optimizing Employee Performance: Communication, Competence, and Job Fit: Meningkatkan Kinerja Karyawan: Peran Komunikasi Efektif, Kompetensi, dan Kesesuaian Jabatan - Muhammad Fatchul Huda; Rifdah Abadiyah (Academia Open, 2022)
This quantitative study investigates the relationship between effective communication, competence, and employee performance, with person-job fit as an intervening variable in a government organization. The research sample comprised 85 employees from the Department of Public Works and Water Resources Development in Sidoarjo. A path analysis technique using Smart-PLS software was employed to analyze the data collected through questionnaires, interviews, and observations. The results highlight the significant positive effects of effective communication and competence on person-job fit, which in turn positively influences employee performance. The findings of this study have implications for organizations seeking to improve employee performance through targeted interventions in communication strategies, competency development, and job-person alignment. Highlights: Effective communication and competence positively impact employee performance. Person-job fit acts as an important intervening variable in the relationship between communication, competence, and employee performance. The findings have implications for organizations aiming to enhance employee performance through targeted interventions in communication strategies, competency development, and job-person alignment. Keywords: Employee performance, Effective communication, Competence, Person-job fit, Government organization.